Pericarditis during infliximab therapy in paediatric ulcerative colitis. (23rd June 2017) - Dipasquale, V.; Gramaglia, S. M. C.; Catena, M. A.; Romano, C.
Summary: What is known and study objective: Infliximab is a widely used drug for treating inflammatory bowel disease (IBD). This drug is known to rarely cause pericarditis in adult populations. Case summary: This report details the case of a 14‐year‐old boy with ulcerative colitis who developed pericarditis after a second infliximab infusion. After discontinuation of therapy, the patient's symptoms were resolved. What is new and conclusion: To our knowledge, this is the first reported paediatric case of pericarditis as a possible complication of infliximab therapy in IBD. Among infliximab‐related delayed adverse reactions, cardiac complications should be monitored in the paediatric population. Abstract : Infliximab, a widely used drug for treating inflammatory bowel disease (IBD), is known to rarely cause pericarditis in adult populations. In this report, we communicate a case of pericarditis after a second infliximab infusion in a 14‐year‐old boy with ulcerative colitis. To our knowledge, this is the first reported paediatric case of pericarditis as a possible complication of infliximab therapy in IBD.